INCREASING THE STUDENTS’ ABILITY IN SPEAKING BY USING TALKING CHIPS TECHNIQUE - Daeli, Hidayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2021)
Speaking is one of the language skills that is very important to the speaker to make communication, express ideas, opinion, and feelings toward the other people orally. In the syllabus of Junior High School hopes that the students are able to speak English fluently, appropriately and accurately. But the fact show that the students are not able to speak English fluently, appropriately and accurately. The purpose of this research is to increase the students’ ability in speaking by using Talking Chips Technique. To achieve the purpose of this research, the researcher applies CAR. The subject of this research is the students at the ninth grade of SMP Negeri 4 Mandrehe which the total number of the students are 30 students. This research is applied in two cycles. Each cycle consists of planning, action, observation, and reflection. The instruments used by the researcher to collect the data are observation paper, field notes, oral test, and camera. Based on the result of the research above, it shows that the students get increasing in speaking and they achieve the Minimum Competence Criterion through Talking Chips Technique. In the other words, Talking Chips Techniques suitable to help the students in getting progression in learning English. So, The researcher suggests the English teachers of SMP Negeri 4 Mandrehe to use Talking Chips Technique to increase the students’ ability in speaking, the teacher should have good preparation before apply Talking Chips Technique in order that he will be succussfull in teaching speaking to students, the teacher should motivate the students to convey their idea during the teaching-learning process, the students should master English vocabularies fluently to help become free and active to express their ability in speaking.